2016
DOI: 10.1002/pola.28197
|View full text |Cite
|
Sign up to set email alerts
|

Poly(ether sulfone)s using a rigid dibenzothiophene dioxide heterocycle

Abstract: Poly(aryl ether)s were prepared by nucleophilic aromatic substitution using conformationally restricted dichloroand difluorodibenzothiophene dioxide heterocyclic monomers with bisphenol A or bisphenol AF. The heterocyclic monomers were prepared from the bis(4-halophenyl) sulfones in two steps via lithiation followed by copper catalyzed intramolecular coupling and characterized by 1 H, 13 C, 19F NMR spectroscopy and GC/MS. Reactivity of the fluorine containing monomer was examined using semi-empirical methods a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…Sulfur-containing polymers are a class of high-performance materials and have been instrumental in the development of specialty applications. While polysulfide (PSR) can be prepared directly from polycondensation, , the direct synthesis of polysulfoxide (PSO) and polysulfone (PSO2) is challenging. , However, the polymers containing sulfur centers with higher oxidation states, polysulfoxide (PSO) and polysulfone (PSO2), display desirable properties, such as thermomechanical and chemical stability. , Other polymers such as those containing phosphorous are also good examples of how the oxidation state of the main chain heteroatom can influence the properties of the polymer …”
Section: Introductionmentioning
confidence: 99%
“…Sulfur-containing polymers are a class of high-performance materials and have been instrumental in the development of specialty applications. While polysulfide (PSR) can be prepared directly from polycondensation, , the direct synthesis of polysulfoxide (PSO) and polysulfone (PSO2) is challenging. , However, the polymers containing sulfur centers with higher oxidation states, polysulfoxide (PSO) and polysulfone (PSO2), display desirable properties, such as thermomechanical and chemical stability. , Other polymers such as those containing phosphorous are also good examples of how the oxidation state of the main chain heteroatom can influence the properties of the polymer …”
Section: Introductionmentioning
confidence: 99%
“…The mechanical strength P1 was slightly higher than that of other polymers, which can probably be due to the higher chain stiffness of P1. Moreover, the mechanical strength of these polymers P2-P4 were higher than that of PA6T-Dupont (the tensile strength was about 50.9 MPa), 24 close to that of PA9T. 23 The result showed that the copolymers had good mechanical property.…”
Section: Mechanical Property Analysismentioning
confidence: 67%
“…into the molecular chain of poly (ether nitrile) (PEN) can improve the solubility, and at the same time can endow it new properties, such as fluorescence properties, 22 antifouling property, 21 and so forth. By introducing hydroquinone, 23 bisphenol A, 24 phenolphthalin, 25 and so forth. into the chain of poly (ether sulfone), the obtained polymer not only has good solubility but also reduces the cost.…”
Section: Introductionmentioning
confidence: 99%